A target enrichment method for gathering phylogenetic information from hundreds of loci: An example from the Compositae1. (6th February 2014) - Mandel, Jennifer R.; Dikow, Rebecca B.; Funk, Vicki A.; Masalia, Rishi R.; Staton, S. Evan; Kozik, Alex; Michelmore, Richard W.; Rieseberg, Loren H.; Burke, John M.
Abstract : Premise of the study: The Compositae (Asteraceae) are a large and diverse family of plants, and the most comprehensive phylogeny to date is a meta‐tree based on 10 chloroplast loci that has several major unresolved nodes. We describe the development of an approach that enables the rapid sequencing of large numbers of orthologous nuclear loci to facilitate efficient phylogenomic analyses. Methods and Results: We designed a set of sequence capture probes that target conserved orthologous sequences in the Compositae. We also developed a bioinformatic and phylogenetic workflow for processing and analyzing the resulting data. Application of our approach to 15 species from across the Compositae resulted in the production of phylogenetically informative sequence data from 763 loci and the successful reconstruction of known phylogenetic relationships across the family. Conclusions: These methods should be of great use to members of the broader Compositae community, and the general approach should also be of use to researchers studying other families.